2007
DOI: 10.1371/journal.pmed.0040353
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Interferon-Beta to Produce a Specific, Multi-Mechanistic Oncolytic Vaccinia Virus

Abstract: BackgroundOncolytic viruses hold much promise for clinical treatment of many cancers, but a lack of systemic delivery and insufficient tumor cell killing have limited their usefulness. We have previously demonstrated that vaccinia virus strains are capable of systemic delivery to tumors in mouse models, but infection of normal tissues remains an issue. We hypothesized that interferon-beta (IFN-β) expression from an oncolytic vaccinia strain incapable of responding to this cytokine would have dual benefits as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
177
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 36 publications
(43 reference statements)
7
177
0
1
Order By: Relevance
“…Pretreatment with cyclophosphamide suppressed the inflammation and resulted in reduced tumor vascular permeability. 30 Kirn et al 31 showed that systemically administered vaccinia virus resulted in infection and subsequent destruction of tumor endothelial cells, which led to loss of tumor vascular density.…”
Section: Targeting the Tumor Microenvironment Enhances Viral Spread Amentioning
confidence: 99%
See 3 more Smart Citations
“…Pretreatment with cyclophosphamide suppressed the inflammation and resulted in reduced tumor vascular permeability. 30 Kirn et al 31 showed that systemically administered vaccinia virus resulted in infection and subsequent destruction of tumor endothelial cells, which led to loss of tumor vascular density.…”
Section: Targeting the Tumor Microenvironment Enhances Viral Spread Amentioning
confidence: 99%
“…42 A vaccinia virus mutant with a deletion in B18R, whose gene product neutralizes type I IFNs, showed IFN-dependent cancer selectivity and efficacy. 31 It has also been shown that adenovirusinduced ERK activation is critical to viral replication. 43 Oncolytic viruses can also be 'programmed' to replicate in cells through certain cellular signaling activities, such as b-catenin, 44 to carry therapeutic transgene that targets tumorigenic pathways, 20 or retargeted to cellular receptors that are essential for signaling (for example, epidermal growth factor receptor (EGFR)).…”
Section: Genetic Engineering Of Oncolytic Viruses Targets Cancer Signmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because they possess the ability to infect a broad range of cell types, only a small amount of virus delivered intravenously will infect the tumor, with the majority undergoing nonpermissive or abortive infections of non-tumor tissue. Therefore, despite the promising results of vaccina virusbased cancer therapies, [14][15][16][17][18] it appears that for effective treatment of cancers it will be necessary to both improve methods of delivery and use of vaccinia in therapeutic combinations.…”
mentioning
confidence: 99%